Deradicalization da'wah: Religious rehabilitation efforts for former terrorism convicts - Rozi, Fachrur; Supena, Ilyas; Riyadi, Agus (Islamic Communication Journal, 2024)
Terrorist acts that often claim religious grounds have become a significant threat to national stability. Based on data from the National Counterterrorism Agency (BNPT), Indonesia, terrorist attacks not only cause casualties but also have an impact on public perception of Islam. This study aims to understand why radical ideology often persists among former terrorist convicts and how deradicalization preaching plays a role in their rehabilitation. This descriptive qualitative study uses a sociological approach, using data collection techniques through observation, interviews, and documentation. The results of the study indicate that radical ideology persists due to limited social support, non-holistic deradicalization programs, ideological backgrounds, and social stigma. External factors such as the lack of special programs, limited officer training, and inconsistent funding also contribute. Deradicalization preaching plays a crucial role by teaching peaceful religious values, empowering socially and economically, reducing social stigma, and involving families and communities. For effective rehabilitation, deradicalization preaching must be holistic, involve various parties, and consider cultural, social, and economic aspects to address the root causes of radicalization. ***** Aksi terorisme yang sering mengklaim landasan agama telah menjadi ancaman besar terhadap stabilitas nasional. Berdasarkan data dari Badan Nasional Penanggulangan Terorisme (BNPT), Indonesia, serangan teror tidak hanya menimbulkan korban jiwa, tetapi juga berdampak pada persepsi publik terhadap Islam. Penelitian ini bertujuan untuk memahami mengapa faham radikal sering kali tetap bertahan di kalangan mantan narapidana terorisme dan bagaimana dakwah deradikalisasi berperan dalam rehabilitasi mereka. Penelitian ini merupakan penelitian kualitatif deskriptif dengan pendekatan sosiologis, menggunakan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa faham radikal tetap bertahan disebabkan oleh dukungan sosial yang terbatas, program deradikalisasi yang tidak holistik, serta latar belakang ideologi dan stigma sosial. Faktor eksternal seperti kurangnya program khusus, keterbatasan pelatihan petugas, dan pendanaan yang tidak konsisten juga berkontribusi. Dakwah deradikalisasi memainkan peran krusial dengan mengajarkan nilai-nilai agama yang damai, memberdayakan secara sosial dan ekonomi, mengurangi stigma sosial, dan melibatkan keluarga serta komunitas. Untuk rehabilitasi yang efektif, dakwah deradikalisasi harus holistik dan melibatkan berbagai pihak, serta mempertimbangkan aspek budaya, sosial, dan ekonomi untuk mengatasi akar penyebab radikalisasi secara menyeluruh.